An unusual new record of Baccharis (Asteraceae) from the Peruvian Andes and its relation with the northern limit of the dry puna - Gonzáles, Paúl; Cano, Asunción; Müller, Jochen (Instituto de Ecología, A.C., 2018)
Background and Aims: The knowledge of the richness and distribution of the flora in the Peruvian Andes is scarce; about 70 taxonomic novelties have been reported for this area in the last decade, a large part belonging to the Asteraceae. The objective of this paper is to contribute to the knowledge of this flora through a new record of Baccharis acaulis. In addition, the distribution pattern of this species is examined.Methods: As part of floristic inventories in the high Andes of Peru, various field trips were carried out, several plant specimens were collected, among them a previously unreported species, which was identified by consulting some specialists and confirmed using taxonomic keys. Furthermore, predicting species distribution based on ecological niche modeling was made use the machine learning algorithm Maxent with the bioclimatic variables of the WorldClim database.Key results: A species of the genus Baccharis was registered for the first time for the flora of Peru. This species is recognized for its unique habit; it is a rhizomatous herb in which the aboveground part consists of small leaf rosettes surrounding a solitary capitulum. The species was collected in the south of the Peruvian Andes. This record extends the known distribution of the species considerably to the north.Conclusions: This record suggests the need to continue studying the Andean flora, as well as the links of their distribution patterns with the phytogeographical regions.